Electrochemical behaviour of titanium in KOH at high potential. (1st June 2016) - Mathis, Aude; Rocca, Emmanuel; Veys-Renaux, Delphine; Tardelli, Joffrey
Highlights: The high potential electrochemical behaviour of Ti depends on the KOH concentration. Intermediate concentrations of KOH favour efficient oxide growth. During voltage linear ramp, current density rises after micro-arc regime initiation. TiO2 layers exhibit n-type semiconductor behaviour according to Mott-Schottky plots. Donor concentration is high (10 22 -10 23 cm −3 ). Abstract: Electrochemical behaviour of pure titanium was studied in KOH-based media over a large voltage range (0-700 V) in order to understand the micro-arc phenomenon occurrence, leading to the formation of a "ceramic-like" oxide layer. The influence of various KOH concentrations in the electrolytic bath (from 0.01 to 0.2 M) was investigated on titanium substrate by a potentiodynamic scan. Whatever the concentration, the electrochemical behaviour of titanium in KOH media can be described in three steps according to voltage: i) a "conventional anodizing" step controlled by the solid-state diffusion of O 2− and Ti 4+ ions under the electric field effect, ii) a voltage range during which the micro-arc phenomenon occurs, named "micro-arc region", iii) a "sharp current rise" induced by the increase of oxide conductivity. After anodizing in galvanostatic conditions, XRD and EDS analyses combined with SEM observations show that all samples have similar morphology with a dense internal layer and a porous external one, constituted by titanium dioxide under anatase and rutile crystallized forms. The electrochemical behaviour of anodized layers was investigated by electrochemical impedance spectroscopy measurements. A Mott-Schottky analysis reveals a n-type semi-conducting behaviour of the oxide layers with a very high donor concentration between 10 22 and 10 23 cm −3 .